2016
DOI: 10.1002/ange.201609636
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Functionalized [3], [4], [5] and [6]Dendralenes through Palladium‐Catalyzed Cross‐Couplings of Substituted Allenoates

Abstract: Amild method for the synthesis of highly functionalized [3]-[6]dendralenes is reported, representing ag eneral strategy to diversely substituted higher homologues of the dendralenes.T he methodology utilizes allenoates bearing various substitution patterns,a long with aw ide range of boron and alkenyl nucleophiles that couple under palladium catalysis leading to sp-, sp 2 -, and sp 3 -substituted arrays. Regioselective transformations of the newly formed unsymmetrical dendralene derivatives are demonstrated. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…To date, [3]­dendralenes or cross-conjugated trienes have been used for the rapid construction of chiral polycyclic structures and play an important role in many fields, such as polymer chemistry, synthetic chemistry, natural product chemistry, and functional materials . In recent years, the synthesis of [3]­dendrarenes has developed rapidly …”
mentioning
confidence: 78%
“…To date, [3]­dendralenes or cross-conjugated trienes have been used for the rapid construction of chiral polycyclic structures and play an important role in many fields, such as polymer chemistry, synthetic chemistry, natural product chemistry, and functional materials . In recent years, the synthesis of [3]­dendrarenes has developed rapidly …”
mentioning
confidence: 78%
“…3h,8 Lipshutz showed that only judiciously designed [3]dendralenic Michael acceptors undergo selective Cu-catalyzed 1,4-or 1,6-conjugate addition (Figure 1B). 9 The development of general catalytic and selective protocols for the functionalization of one specific alkene in minimally biased [n]dendralenes remains elusive.…”
mentioning
confidence: 99%